Larvul Ngabal Law as A Regulation in Marine Resources Management In Kei Islands, Southeast Maluku Regency - Angga, La Ode; Latupono, Barzah; Renuat, Ahmad Yani; Atbar, Rini (Batulis Civil Law Review, 2024)
Introduction: Hawear Customary Law has long been known in Southeast Maluku and has a rolewhich is important in organizing life, especially for traditional law communities. Hawear contains meaning prohibition to take natural resources on land or in the sea, which is based on several important and basic arguments. The principle that is the basis for the actual existence of Hawear's lais the principle of sustainablemanagement of natural resources. Wise thinking that develops wiselyThis local area is also based on the economic aspects of the country's community and the villages and villages located in the area small islands.Purposes of the Research: To find out and analyze Hawear's existence in protecting and preserving marine genetic resources in Southeast Maluku Regency.Methods of the Research: The approach method used in this research is sociological juridical which is a descriptive qualitative analysis study. This research seeks to describe what occurs in the Kei Indigenous Community in Southeast Maluku Regency, it is related to resource management coastal and marine power. The data collection techniques used in this research are: Interview, questionnaire and literature study.Results of the Research: The existence or existence of law Larvul Ngabal Currently, it is increasingly existing, this can be seen from the increasingly advanced society of Southeast Maluku and have the same feelings in a group, where they stay in one place because they come from from the same genealogy or descent. They have their own customary laws that regulate them regarding rights and obligations regarding material and immaterial goods. They also have social institutions, traditional leadership, and traditional justice recognized by the group. Larvul Nabalas a form of rule which the people of Southeast Maluku use in managing their marine resources is expected to remain the same obeyed so that it becomes a law in the management of resources both at sea and on land so that they are maintained natural sustainability. This is also in line with the protection of indigenous communities which has been recognized in Article 18B paragraph (2) and Article 28I paragraph (3) in the Indonesian Constitution The Constitution of the Republic Indonesia in 1945 (1945 Constitution of the Republic of Indonesia). This means that the state has recognized and respected rights indigenous communities, including the Law Society Larvul Ngabal.